Eksistensialisme Mulla Sadra - Faiz, Faiz (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This article seeks to analyze Mulla Sadra?s philosophical existentialism. Sadra seeks to provide answers to formulate a concept called the philosophy of wisdom. In outline the teaching philosophy of Sadra include authenticity of the form (asâlat al-wujûd) that the answer to differences in the methods used by the essentialist and existentialist. In this case authenticity of the form (asâlat al-wujûd) spawned several sections related to each other, among other pantheism (wahdat al-wujûd), doubts exist (tashkîk al-wujûd), and movement core (al-harakah al-jawharîyah). Through wahdat al-wujûd (pantheism), Sadra then change the view of the beginning made authenticity essence (asâlat al-mâhîyah) as the core of the reality to an authenticity presence (asâlat al-wujûd). As for tashkîk al-wujûd (doubts exist) is in response to the notion that ?form? is God, while the universe is a shadow of it. Sadra gives a different view, he said the absence of the universe (reality) man can not find the ?form? the truth, the God who became a grand synthesis of some of the concepts put forward by Islamic thinkers.